PENGARUH KOMPETENSI KOMUNIKASI, KECERDASAN EMOSIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA PERSONEL POLSEK KEDUNDUNG KABUPATEN SAMPANG - jurnalmap map; Ali Sibro Mulisi; Nugroho Mardi Wibowo; Muninghar ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2019)
ABSTRACT This research was conducted at Kedungdung Sub-District Police, Sampang Regency. with a total sample of 33 people. The objectives of this study are: 1) To find out and describe communication competencies, emotional intelligence, organizational culture and performance of police officers, 2) To find out and analyze whether communication competencies, emotional intelligence and organizational culture simultaneously influence the performance of police officers, 3) To find out and analyze whether communication skills, emotional intelligence and organizational culture partially influence the performance of police officers. The results showed that 1) Simultaneously, communication competencies, emotional intelligence and organizational culture had a very significant effect on employee performance, 2) Partially, communication competencies, emotional intelligence and organizational culture have a significant influence on the performance Police officers. Keywords: Competence of Communication, Emotional Intelligence, Organizational Culture and Performance of Personnel.